REIMAGINING DOMESTICITY: ANALYZING GENDER INEQUALITY AND PATRIARCHAL NORMS IN THE GREAT INDIAN KITCHEN AND ITS REFLECTION IN INDIAN LITERATURE AND CINEMA - George, Roselin Linitta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the context of Indian society, gender inequality has often been tied to domesticity, where the roles of women in the kitchen and home have been stereotyped and enforced for generations. Films and literature have long depicted the nuances of this inequality, offering a lens through which to critique the rigid gender norms that shape domestic spaces. The Malayalam film The Great Indian Kitchen (2021), directed by Jeo Baby, provides a poignant exploration of these themes, focusing on the experiences of a young woman who, after marriage, is subjected to the exhausting and largely invisible labor of the kitchen. This paper seeks to explore how The Great Indian Kitchen critiques the patriarchal norms that govern domesticity in India. By analyzing the film alongside representations of women in Indian literature and cinema, this paper will explore the intersection of gender, domestic labor, and patriarchal structures in the Indian sociocultural context. The primary aim of this paper is to critically examine how The Great Indian Kitchen subverts the traditional portrayal of domesticity in Indian culture. Additionally, it will explore the way this film fits into a broader discourse on gender inequality in Indian literature and cinema. The paper will also analyze the social critique embedded in the film, demonstrating how The Great Indian Kitchen challenges patriarchal ideologies by centering the domestic space as a site of both oppression and potential resistance.